Modeling Chikungunya control strategies and Mayaro potential outbreak in the city of Rio de Janeiro - Dodero-Rojas, Esteban; Ferreira, Luiza G.; Leite, Vitor B.P. [UNESP]; Onuchic, José N.; Contessoto, Vinícius G. (Public Library of Science (PLoS), 2020)
Mosquito-borne diseases have become a significant health issue in many regions around the world. For tropical countries, diseases such as Dengue, Zika, and Chikungunya, became epidemic in the last decades. Health surveillance reports during this period were crucial in providing scientific-based information to guide decision making and resources allocation to control outbreaks. In this work, we perform data analysis of the last Chikungunya epidemics in the city of Rio de Janeiro by applying a compartmental mathematical model. Sensitivity analyses were performed in order to describe the contribution of each parameter to the outbreak incidence. We estimate the basic reproduction number for those outbreaks and predict the potential epidemic outbreak of the Mayaro virus. We also simulated several scenarios with different public interventions to decrease the number of infected people. Such scenarios should provide insights about possible strategies to control future outbreaks.